P-022 Flow Diversion in the Posterior Circulation: A Single Center Experience and Literature Review. (26th July 2014) - Toth, G; Bain, M; Hussain, S; Moskowitz, S; Rasmussen, P; Masaryk, T; Hui, F
Abstract : Introduction: Flow diverters have been increasingly utilised for the treatment of large intracranial aneurysms, predominantly in the anterior circulation. There is limited data available on the safety and efficacy of this treatment approach for posterior circulation aneurysms, which often times have limited therapeutic options and unfavorable natural history. Objective: The goal of this study is to present our posterior circulation flow diverter experience in comparison with recent studies. We also discuss the potential role of platelet inhibition testing, adjunctive coiling and the relevance of aneurysm type in clinical outcome. Methods: This is a retrospective review of 6 patients with 7 aneurysms (5 saccular, 2 fusiform) in posterior circulation vessels, treated with flow diverter technology. We compare our results to available studies in the current literature. Results: Pre-procedure platelet inhibition testing was routinely utilised. The average largest aneurysm diameter was 19.5 mm, and aneurysm length was up to 52 mm. None of the aneurysms were acutely ruptured, but one patient had a history of prior subarachnoid haemorrhage. Locations included 3 basilar artery, 3 distal vertebral artery and 1 posterior cerebral artery aneurysms. An average of 2 flow diverters were placed successfully in all patients. Adjunctive coiling was utilised in 3 (42.9%) cases. Imaging and clinical follow up was available in all 7 cases, ranging from 3.5 to 25 months (mean 10.1 months). Complete angiographic occlusion was seen in 3 out of 7 cases (42.9%), and another 3 aneurysms 42.9%) had decreased residual filling on follow-up. The one remaining patient had no clinical complications and no change in aneurysm filling initially after the procedure, but developed in-stent thrombosis with large brainstem stroke at 4.5 months, a week after he self-discontinued his dual antiplatelet therapy. Other clinical events included one patient with a periprocedural stroke with moderate residual deficits, and 2 other patients with a small periprocedural stroke with complete recovery. One of the latter 2 patients developed acute intraprocedural in-stent thrombosis with transient symptoms, which was rapidly treated, and had no significant long-term clinical consequences. There was no death, distal parenchymal haemorrhage or delayed aneurysm rupture. Overall 4 out of 6 patients, or 5 of 7 cases (71%), had good clinical outcome (mRS 0–1), all with saccular type aneurysms. Conclusion: Posterior circulation flow diversion carries risks, but may represent a reasonable treatment option in carefully selected patients with high-risk aneurysms, which otherwise have and poor natural history and no optimal treatment strategy. Further data is necessary to assess the role of flow diversion in the posterior circulation. Disclosures: G. Toth: None. M. Bain: None. S. Hussain: None. S. Moskowitz: None. P. Rasmussen: 1; C; ev3/Codman. 2; C; Codman. 4; C; Penumbra. 6; C; Blockade Medical. T. Masaryk: None. F. Hui: None.